Enhancement of catalytic durability through nitrogen-doping treatment on the CNF-derivatized ACF support for high temperature PEMFC. (4th May 2016) - Jeon, Yukwon; Park, Joo-Il; Ok, Jinhee; Dorjgotov, Altansukh; Kim, Hyun-Jong; Kim, Hyeongsu; Lee, Chanmin; Park, Sangsun; Shul, Yong-Gun
Abstract: As a new carbon support for high temperature – proton exchange membrane fuel cell (HT-PEMFC), the nitrogen doped CNF/ACF (N/CNF/ACF) was synthesized by coating and annealing the polypyrrole to the surface of carbon nanofiber (CNF) grown on activated carbon fiber (ACF). The durability and electrochemical performance of Pt/N/CNF/ACF and commercial Pt/C was examined and compared with various analytical tools as well as accelerated life-time test (ALT) at high temperature of 120 °C. The catalytic durability on Pt/N/CNF/ACF was improved due to the enhanced π-bonding and the basic electron donor property of nitrogen contents. Such stability of Pt/N/CNF/ACF was originated from the strong interaction between Pt particles and carbon matrix with nitrogen contents. The evidences on the nitrogen effect of Pt/N/CNF/ACF were elucidated with the gentle loss of electrochemical active surface area (ECSA) and the shift of XPS peak (Pt 4f) to the direction of higher binding energy, comparing with those of commercial Pt/C, before and after ALT. The physical and chemical properties on the Pt/N/CNF/ACF was characterized with HR-TEM, FE-SEM, FT-IR, XRD and XPS, in detail. And, their electrochemical properties for HT-PEMFC were examined with single cell and half cell test, before and after ALT. Graphical abstract: Illustration of the MEA composition using developed Pt/N/CNF/ACF. Highlights: The N-doped (PPy) carbon (N/CNF/ACF) was newly synthesized for applying to PEMFC. This carbon was applied to accelerated life-time test at high temperature of 120 °C. This carbon showed good catalytic durability, comparing to commercial Pt/C.